Accommodative Lag Persistence in Treated Anisometropic, Strabismic, and Mixed Amblyopia - Jit B. Ale Magar; Shaheen P. Shah (Journal of Ophthalmology)
Background. Amblyopic eyes typically exhibit greater lag of accommodation. Whether this improves after amblyopia treatment is inconclusive. The aim of this study is to report post-treatment accommodative response in amblyopia and to investigate if the lag is associated with visual acuity, treatment duration, and amblyopia type. Methods. Monocular and binocular accommodative responses were measured using Nott’s method of dynamic retinoscopy in amblyopia of anisometropic, strabismic, and combined anisometropic-strabismic types and age-matched controls with normal vision. The results were compared using the nonparametric Wilcoxon signed ranks test. Linear regression analysis was used to examine association of the lag to refractive error, duration of therapy, and visual acuity. Results. Mean ± SD age of 46 amblyopic and 20 control subjects were 6.9 ± 1.8 and 6.9 ± 2.2 years, respectively. At the time of the study, 30 amblyopic subjects were receiving patching therapy and ceased in the remainder. In amblyopic eyes, mean ± SD monocular and binocular lags were 1.2 ± 0.6D and 1.0 ± 0.5D (p<0.001), respectively, compared to 0.6 ± 0.3D and 0.5 ± 0.2D (p<0.005), respectively, in nonamblyopic eyes and 0.4 ± 0.2D and 0.3 ± 0.2D (p=0.093), respectively, in the controls. By types, the monocular lag was significantly higher than the binocular lag (p=0.001) in mixed amblyopia (p=0.004); they were similar in anisometropic (p=0.283) and strabismic (p=0.743) amblyopia. Monocular lag was significantly correlated to BCVA (r = 0.46; p=0.001) and refraction (r = 0.42; p=0.001) but not to patching duration (r = 0.1; p=0.280). Conclusion. Inadequate accommodative response, a higher lag, persists in amblyopic eyes even after the treatment. Impaired accommodative response is partly determined by posttherapy visual acuity. Further studies investigating the effect of accommodative lag on visual recovery and whether optical correction of the deficiency may improve visual outcome of the treatment are recommended.